COMPETENCY AND QUALITY OF STATE MADRASAH TEACHERS IN BANTEN PROVINCE - Ratu Bai Rohimah (Jurnal Visi Ilmu Pendidikan, 2023)
This study aims to describe and analyze teacher resources based on the suitability of the placement and needs of teachers in madrasas at the secondary education level (MTsN) in Banten Province. In particular, this study aims to analyze the qualifications of linear teacher education with the fields of study being taught so that teacher competencies and teacher resource maps are seen at the MTsN level in Banten. This research was a qualitative research, where the data obtained are based on the results of surveys, interviews and questionnaires, which were processed and interpreted. Data were obtained from 33 MTsN education units in Banten Province. The results of the study showed that the number of madrasa teachers in Banten had fulfilled the requirements as educators, namely 1,024 were S1 graduates and 181 were S2 graduates. There are 967 teachers who have been certified and 205 who have not certified. The madrasa teachers who have not been certified are generally in South Banten, Lebak and Pandeglang. This means that the linearity of education and the subjects taught still needs to be pursued at madrasas in Pandeglang and Lebak. Regarding the ratio of teachers to students at public madrasas in Banten Province, it was ideal, which was 1:20 except for a few madrasas in the Lebak area.